SoHor (Sosog Horticulture) as a Food Sustainability in the New Normal Period in Tanjungsari Village, Rajadesa District, Ciamis Regency - Nana Nana; Yanti Sofi Makiyah; Ernita Susanti; Dwi Sulistyaningsih; Suera Sarah Budiaman; Muhammad Nurkholis Dzikri Alfauzi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Covid-19 pandemic has caused a decline in people's purchasing power, especially for household consumption. Therefore, to alleviate the impact of the Covid-19 pandemic, the community is directed to be able to meet food needs through food security. The purpose of this service is to provide training on horticultural crop cultivation using sosog to the people of Tanjungsari Village, Rajadesa District, Ciamis Regency. The method used is by way of material presentation, question and answer and guided training. After the training activities were carried out, there was an increase in community knowledge and skills both in terms of knowledge about the types and benefits of horticultural plants and how to grow horticultural crops using sosog along with how to care for them. The community gave a positive response to the activities carried out. This activity is considered useful by the community and is a form of optimizing the potential of the Tanjungsari Village community, most of which are farmers and woven bamboo craftsmen to be able to meet food needs through sosog as a planting medium.